Determinants of clinical course and mortality in COVID-19 patients with hematological disorders: real life data from a single center - Deveci, Burak; Döşemeci, Levent; Aslan, Ayşe; Asal, Gökhan; Üstün, Bilge; Yıldırmer Akar, Meltem; Toptas, Tayfur; Yavuz Taşlıpınar, Mine; Saba, Rabin (The European Research Journal, 2022)
Objectives: Patients with hematological disorders are often immunosuppressive due to underlying diseases, immunosuppressive therapies or cytotoxic chemotherapeutics. In the case of coronavirus disease 2019 (COVID-19), they are at high risk of poor prognosis. Therefore, the present study aimed to evaluate the determinants of clinical course and mortality in COVID-19 patients with hematological disorders. Methods: Sixty-two hospitalized patients older than 18 years with documented COVID-19 and hematological disorders were included in the study. The clinical and laboratory data of the patients were recorded. Age, gender, overall follow-up time, duration of hospitalization, neutropenia, D-dimer levels, disease status, presence of underlying diseases, prior autologous and allogeneic stem cell transplant, immunosuppressive drug use, chemotherapy within 28 days, pneumonia, secondary bacterial infection, intubation, survival and mortality of the patients were evaluated. Results: Twenty-eight (45.2%) of 62 patients died due to COVID-19 and its complications. It was observed that presence of pneumonia, secondary bacterial infection, intubation, neutropenia developed after the diagnosis of COVID-19, and elevated D-dimer levels were associated with significant mortality. A D-dimer level of >1.2 μg/dL was found to be associated with 5.02 fold increase in the risk of death, with 60.7% sensitivity and 76.5% specificity. Presence of rheumatologic diseases also affected survival negatively. Conclusions: D-dimer levels have high predictive value for mortality. Considering the identified risk factors, it can be concluded that broad spectrum antibiotics can be administered earlier for prevention of high mortality rates in COVID-19 patients with underlying hematological disorders. These observations can give confidence to clinicians that delivery of effective anticancer regimens should continue during this difficult pandemic.